Analysis of The Economic Value Added (EVA) Method as A Measurement of Financial Performance at PT X Indonesia - Jaka Maulana; Cahyat Rohyana; Rukmi Juwita (Universitas Pendidikan Indonesia, 2023)
Performance appraisal of a company is very important and the appraisal process must be in line with effectiveness and efficiency in achieving competitive advantage in the business world. The concept of Economic Value Added (EVA) as an alternative to value-based performance measurement is a measure of the economic added value generated by a company as a result of management activities or strategies. With EVA, company owners will only value activities that add value and discard activities that damage or reduce the value of the company as a whole. PT X Indonesia is engaged in Warehousing and Distribution, becoming a promising business in the development of Distribution and Warehousing in Indonesia. The data analysis method in this study is quantitative analysis based on secondary data from the financial statements of PT X. The population of this study is a logistics service provider company at PT X Indonesia for the 2018-2020 financial statements. The results of the calculation of economic value added in 2018, 2019, 2020 based on the audited financial statements of PT X Indonesia show an EVA value below 0 or negative EVA for 2020, but for 2018 and 2019 is positive EVA. This results in the process of adding to the company's economic value not occurring, which means that the profits generated each year cannot meet the expectations of creditors and company shareholders (investors) for 2020.